The global prevalence of hepatitis D virus infection: Systematic review and meta-analysis - Stockdale, Alexander J.; Kreuels, Benno; Henrion, Marc Y.R.; Giorgi, Emanuele; Kyomuhangi, Irene; de Martel, Catherine; Hutin, Yvan; Geretti, Anna Maria (Journal of hepatology, 2020)
There are uncertainties about the epidemic patterns of HDV infection and its contribution to the burden of liver disease. We estimated the global prevalence of HDV infection and explored its contribution to the development of cirrhosis and hepatocellular carcinoma (HCC) among HBsAg-positive people. We searched Pubmed, EMBASE and Scopus for studies reporting on total or IgG anti-HDV among HBsAg-positive people. Anti-HDV prevalence was estimated using a binomial mixed model, weighting for study quality and population size. The population attributable fraction (PAF) of HDV to cirrhosis and HCC among HBsAg-positive people was estimated using random effects models. We included 282 studies, comprising 376 population samples from 95 countries, which together tested 120,293 HBsAg-positive people for anti-HDV. The estimated anti-HDV prevalence was 4.5% (95% CI 3.6–5.7) among all HBsAg-positive people and 16.4% (14.6–18.6) among those attending hepatology clinics. Worldwide, 0.16% (0.11–0.25) of the general population, totalling 12.0 (8.7–18.7) million people, were estimated to be anti-HDV positive. Prevalence among HBsAg-positive people was highest in Mongolia, the Republic of Moldova and countries in Western and Middle Africa, and was higher in injecting drug users, haemodialysis recipients, men who have sex with men, commercial sex workers, and those with HCV or HIV. Among HBsAg-positive people, preliminary PAF estimates of HDV were 18% (10–26) for cirrhosis and 20% (8–33) for HCC. An estimated 12 million people worldwide have experienced HDV infection, with higher prevalence in certain geographic areas and populations. HDV is a significant contributor to HBV-associated liver disease. More quality data are needed to improve the precision of burden estimates. We combined all available studies to estimate how many people with hepatitis B also have hepatitis D, a viral infection that only affects people with hepatitis B. About 1 in 22 people with hepatitis B also have hepatitis D, increasing to 1 in 6 when considering people with liver disease. Hepatitis D may cause about 1 in 6 of the cases of cirrhosis and 1 in 5 of the cases of liver cancer that occur in people with hepatitis B. Hepatitis D is an important contributor to the global burden of liver disease. [Display omitted] •HDV infection is common among HBsAg-positive people worldwide.•Among HBsAg-positive people, estimated HDV prevalence is 4.5% (95% CI 3.6–5.7).•HDV prevalence in HBsAg-positive hepatology clinic attendees is 16.4% (14.6–18.6).•HDV prevalence is higher in people who inject drugs and who have HCV or HIV.•HDV causes an estimated 18% of cirrhosis and 20% of HCC associated with hepatitis B.